2019
DOI: 10.1017/s0033291719001557
|View full text |Cite
|
Sign up to set email alerts
|

Stressful life events moderate the effect of neural reward responsiveness in childhood on depressive symptoms in adolescence

Abstract: BackgroundReward processing deficits have been implicated in the etiology of depression. A blunted reward positivity (RewP), an event-related potential elicited by feedback to monetary gain relative to loss, predicts new onsets and increases in depression symptoms. Etiological models of depression also highlight stressful life events. However, no studies have examined whether stressful life events moderate the effect of the RewP on subsequent depression symptoms. We examined this question during the key develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
36
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 60 publications
9
36
2
Order By: Relevance
“…Animal and human studies have demonstrated that stress can reduce striatal reward responses (88)(89)(90)(91)(92)(93). The relationship may be more complicated in that a genetic predisposition to RPAs may represent a vulnerability to depression when exposed to a stressful environment (23,30,94). An immediate research need is a twin study to test the genetic and environmental origins of the covariation between depression and reward processing.…”
Section: Origins Of Rpas and Depressionmentioning
confidence: 99%
“…Animal and human studies have demonstrated that stress can reduce striatal reward responses (88)(89)(90)(91)(92)(93). The relationship may be more complicated in that a genetic predisposition to RPAs may represent a vulnerability to depression when exposed to a stressful environment (23,30,94). An immediate research need is a twin study to test the genetic and environmental origins of the covariation between depression and reward processing.…”
Section: Origins Of Rpas and Depressionmentioning
confidence: 99%
“…Several researchers have posed a reward mediation model of depression, such that acute and chronic stress contribute to reward dysfunction, which, in turn, can lead to the development of depression (e.g., Auerbach et al, 2014). Stressful life events have also been shown to moderate the effect of neural response to reward on depression symptoms longitudinally, such that a blunted reward response (RewP) in combination with stressful life events predicted higher depression symptoms at follow-up (Goldstein et al, 2020). There is also evidence that these effects can operate on shorter time scales.…”
Section: Interactions Across Functional Domains: Reward and Stressmentioning
confidence: 99%
“…Similar to findings from neuroimaging studies examining brain regions involved in reward processing, research investigating RewP has found that a reduced RewP to monetary rewards prospectively predicts depressive symptoms across childhood and adolescence (Bress et al, 2015; Nelson et al, 2016; Kujawa et al, 2019). Additionally, recent research has shown that RewP to monetary reward measured in childhood interacts with acute stressful events to predict depressive symptoms in early adolescence (Goldstein et al, 2019). However, it remains unclear how this manifests with regard to social reward and to specific types of stressful experiences, as well as the extent to which reduced reward responsiveness as measured by RewP reflects a moderator or mechanism of the effects of stress on depressive symptoms.…”
Section: Introductionmentioning
confidence: 99%